2020
DOI: 10.3892/or.2020.7885
|View full text |Cite
|
Sign up to set email alerts
|

Identification of in vitro and in vivo oncolytic effect in colorectal cancer cells by Orf virus strain NA1/11

Abstract: Orf virus (ORFV) is a favorable oncolytic viral carrier in research, and ORFV strain NZ2 has been revealed to have antitumor effects in animal models mediated by immunoregulation profile. However, the antitumor effects triggered by the ORFV in colorectal cancer (CRC) cells is poorly characterized. The in vivo and in vitro roles of ORFV in CRC were determined using western blotting, colony formation, CCK-8, wound scratch assay, qPCR, and animal models. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…After the virus infects cells, it immediately induces robust death, and there are no oncogenes associated with the virus that might cause secondary tumorigenesis. The abnormal replication of tumor cells and the enrichment of some receptors on their surface create a microenvironment favoring viral replication that makes CVB3 better able to infect these hyperactive cells, causing apoptosis, pyroptosis, necrosis, or cell cycle arrest [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the virus infects cells, it immediately induces robust death, and there are no oncogenes associated with the virus that might cause secondary tumorigenesis. The abnormal replication of tumor cells and the enrichment of some receptors on their surface create a microenvironment favoring viral replication that makes CVB3 better able to infect these hyperactive cells, causing apoptosis, pyroptosis, necrosis, or cell cycle arrest [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Orf virus (ORFV) can rapidly mediate innate and adaptive immune responses in vivo, so it has been proposed as a potential oncolytic virus vector. Studies have demonstrated that ORFV strain NA1/11 can inhibit CRC growth and metastasis by inducing apoptosis in CRC cells (27). In addition, a research team (28) produced M51R genetically engineered recombinant virus from cDNA clones containing the M protein mutation to construct M51R vesicular stomatitis virus (M51R VSV), which inhibits CRC peritoneal surface spread (PSD).…”
Section: Other Virusesmentioning
confidence: 99%
“…Oncolytic viruses are usually natural or modified viruses that target and kill tumor cells. These viruses regulate key intracellular processes and anti-viral responses such as apoptosis, inflammation, angiogenesis, and the cell cycle (Chen et al, 2021). Also, oncolytic viruses can enhance the host's anti-tumor immunity through multiple mechanisms (Ramelyte et al, 2021).…”
Section: Introductionmentioning
confidence: 99%